Courses for Kids
Free study material
Offline Centres
Store Icon

How do you find the zeroes of $f\left( x \right)={{x}^{2}}-5x-6$ by factoring?

Last updated date: 13th Jun 2024
Total views: 372k
Views today: 10.72k
372k+ views
Hint: We use both grouping method and vanishing method to solve the problem. We take common terms out to form the multiplied forms. Factorising a polynomial by grouping is to find the pairs which on taking their common divisor out, give the same remaining number. In the case of vanishing method, we use the value of $x$ which gives the polynomial value 0.

Complete step by step solution:
We apply the middle-term factoring or grouping to factorise the polynomial.
In case of ${{x}^{2}}-5x-6$, we break the middle term $-5x$ into two parts of $-6x$ and $x$.
So, ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6$. We have one condition to check if the grouping is possible or not. If we order the individual elements of the polynomial according to their power of variables, then the multiple of end terms will be equal to the multiple of middle terms.
Here multiplication for both cases gives $-6{{x}^{2}}$. The grouping will be done for ${{x}^{2}}-6x$ and $x-6$.
We try to take the common numbers out.
For ${{x}^{2}}-6x$, we take $x$ and get $x\left( x-6 \right)$.
For $x-6$, we take 1 and get $\left( x-6 \right)$.
The equation becomes ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6=x\left( x-6 \right)+\left( x-6 \right)$.
Both the terms have $\left( x-6 \right)$ in common. We take that term again and get
  & {{x}^{2}}-5x-6 \\
 & =x\left( x-6 \right)+\left( x-6 \right) \\
 & =\left( x-6 \right)\left( x+1 \right) \\
Therefore, $\left( x+1 \right)\left( x-6 \right)=0$ has multiplication of two polynomials giving a value of 0. This means at least one of them has to be 0.
So, values of x are $x=6,-1$.
We know for a general equation of quadratic $a{{x}^{2}}+bx+c=0$, the value of the roots of x will be $x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.
In the given equation we have ${{x}^{2}}-5x-6=0$. The values of a, b, c are $1,-5,-6$ respectively.
We put the values and get x as $x=\dfrac{-\left( -5 \right)\pm \sqrt{{{\left( -5 \right)}^{2}}-4\times 1\times \left( -6 \right)}}{2\times 1}=\dfrac{5\pm \sqrt{49}}{2}=\dfrac{5\pm 7}{2}=6,-1$.

Note: We find the value of x for which the function $f\left( x \right)={{x}^{2}}-5x-6$. We can see $f\left( 6 \right)={{6}^{2}}-5\times 6-6=36-30-6=0$. So, the root of the $f\left( x \right)={{x}^{2}}-5x-6$ will be the function $\left( x-6 \right)$. This means for $x=a$, if $f\left( a \right)=0$ then $\left( x-a \right)$ is a root of $f\left( x \right)$. We can also do the same process for $\left( x+1 \right)$.